2012
DOI: 10.1177/1362361312464529
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and within-family associations in the broad autism phenotype

Abstract: While there is a strong sex bias in the presentation of autism, it is unknown whether this bias is also present in subclinical manifestations of autism among relatives, or the broad autism phenotype (BAP). This study examined this question, and investigated patterns of co-occurrence of BAP traits within families of individuals with autism. Pragmatic language and personality features of the BAP were studied in 42 fathers and 50 mothers of individuals with autism using direct assessment tools used in prior famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 54 publications
(117 reference statements)
6
24
0
Order By: Relevance
“…This study examined shared familial transmission and cross‐assortative mating of ASD and anxiety symptoms as possible explanations for the frequent co‐occurrence of ASD and anxiety. In line with the literature regarding familial transmission of ASD symptoms (Constantino & Todd, ; De la Marche et al., ; Klusek et al., ; Lyall et al., ; Maxwell et al., ) and anxiety symptoms (Beidel & Turner, ; Last et al., ), we found that parental ASD and anxiety symptoms predicted similar symptoms in children, although results differed depending on the informant type. No clear parent‐of‐origin effects were found in the transmission of symptoms from parents to children.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study examined shared familial transmission and cross‐assortative mating of ASD and anxiety symptoms as possible explanations for the frequent co‐occurrence of ASD and anxiety. In line with the literature regarding familial transmission of ASD symptoms (Constantino & Todd, ; De la Marche et al., ; Klusek et al., ; Lyall et al., ; Maxwell et al., ) and anxiety symptoms (Beidel & Turner, ; Last et al., ), we found that parental ASD and anxiety symptoms predicted similar symptoms in children, although results differed depending on the informant type. No clear parent‐of‐origin effects were found in the transmission of symptoms from parents to children.…”
Section: Discussionsupporting
confidence: 90%
“…Statistically significant coefficients are presented in bold. Klusek et al, 2014;Lyall et al, 2014;Maxwell et al, 2013) and anxiety symptoms (Beidel & Turner, 1997;Last et al, 1991), we found that parental ASD and anxiety symptoms predicted similar symptoms in children, although results differed depending on the informant type. No clear parent-oforigin effects were found in the transmission of symptoms from parents to children.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Atypical pragmatic features such as echolalia, perseveration, and bizarre word choice are seen at increased rates in ASD (Ghaziuddin & Leonore, 1996; Ross, 2002; Schuler & Prizant, 1985), and narrative (storytelling) skills are impaired as well (Capps, Losh, & Thurber, 2000; Diehl, Bennetto, & Young, 2006; Losh & Capps, 2003; Loveland, McEvoy, & Tunali, 1990; Tager-Flusberg, 1995). Differences in pragmatic language use are thought to be a genetically meaningful feature of ASD, given that subclinical pragmatic differences present at increased rates among unaffected relatives of individuals with ASD (Landa et al, 1992; Losh, Childress, Lam, & Piven, 2008) and show patterns suggestive of intrafamilial transmission (Klusek, Losh, & Martin, 2012). …”
Section: Pragmatic Language In Asd and Fxsmentioning
confidence: 99%
“…It is important to note that elements of the BAP may be present in any family-they are not restricted to families raising children with ASD. Several studies have addressed the BAP within general populations [e.g., Klusek, Losh, & Martin, 2014;Swanson, Serlin, & Siller, 2013]. Given our sampling constraints (data utilized from an existing infant sibling study), addressing the BAP in first-born children or more general populations (e.g., as discussed in Landry & Chouinard, 2016) was beyond the scope of the current study.…”
Section: Defining the Bapmentioning
confidence: 99%